Acoustofluidics - Friend, James (Frontiers in Acoustics, 2023)
The propagation of acoustic waves in fluids and solids produces fascinating phenomena that have been studied since the late 1700's and through to today, where it is finding broad application in manipulating fluids and particles at the micro to nano-scale. Due to the recent and rapid increase in application frequencies and reduction in the scale of devices to serve this new need, discrepancies between theory and reality have driven new discoveries in physics that are underpinning the burgeoning discipline. While many researchers are continuing to explore the use of acoustic waves in microfluidics, some are exploring vastly smaller scales, to nanofluidics and beyond. Because many of the applications incorporate biological material-organelles, cells, tissue, and organs-substantial effort is also being invested in understanding how ultrasound interacts with these materials. Surprisingly, there is ample evidence that ultrasound can be used to directly drive cellular responses, producing a new research direction beyond the established efforts in patterning and agglomerating cells to produce tissue. We consider all these aspects in this mini-review after a brief introduction to acoustofluidics as an emerging research discipline.